2005
DOI: 10.1021/np0502241
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Epipolysulfanyldioxopiperazines from Gliocladium roseum

Abstract: Five new verticillin-type epipolysulfanyldioxopiperazines, gliocladine A (1), B (2), C (3), D (4), and E (5), were isolated from wheat solid-substrate fermentation of Gliocladium roseum 1A, along with four known compounds, verticillin A (6), 11'-deoxyverticillin A (7), Sch52900 (8), and Sch52901 (9). Their structures were elucidated by extensive 1D and 2D NMR studies, MS, and chemical transformations. In vitro immersion tests showed that all nine compounds exhibited antinematodal activity against Caenorhabditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(121 citation statements)
references
References 14 publications
2
117
0
2
Order By: Relevance
“…[16][17][18][19][20][21][22] In okaramines the HPIC is condensed to a diketopiperazine (DKP) unit formed from a second amino acid. Leptosins D-F (12)(13)(14), [23] gliocladines C-E (15-17), [24] gliocladins A-C, [25] plectosphaeroic acids A-C (18,19), [26] (+)-asperazine (20), [27] and naseseazines A and B [28] have an analogous DKP unit containing an extra indole, bound between C 3 and C 3a (except for in the case of (+)-asperazine and the naseseazines, in which the indole binds via C 7 and C 6 , respectively). Brevicompanines A-H (21: A, 22: B), allo-brevicompanine B and fructigenine B [29][30][31] are also alkylated at C 3a ; as is ardeemin, isolated from a strain of Aspergillus fischeri; [32] roquefortines C, D (23), F and G; [33][34][35][36] and aszonalenin (24).…”
Section: Structure and Bioactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22] In okaramines the HPIC is condensed to a diketopiperazine (DKP) unit formed from a second amino acid. Leptosins D-F (12)(13)(14), [23] gliocladines C-E (15-17), [24] gliocladins A-C, [25] plectosphaeroic acids A-C (18,19), [26] (+)-asperazine (20), [27] and naseseazines A and B [28] have an analogous DKP unit containing an extra indole, bound between C 3 and C 3a (except for in the case of (+)-asperazine and the naseseazines, in which the indole binds via C 7 and C 6 , respectively). Brevicompanines A-H (21: A, 22: B), allo-brevicompanine B and fructigenine B [29][30][31] are also alkylated at C 3a ; as is ardeemin, isolated from a strain of Aspergillus fischeri; [32] roquefortines C, D (23), F and G; [33][34][35][36] and aszonalenin (24).…”
Section: Structure and Bioactivitymentioning
confidence: 99%
“…These include the neurokinin antagonists (+)-WIN64 821 (38) and (+)-WIN64 745 (39), both isolated from a strain of Aspergillus sp. ; [64][65][66] (À)-ditryptophenaline (40), obtained from Aspergillus flavus; [67] the antiviral agent (+)-asperdimin (41), isolated from extracts of Aspergillus niger; [68] chaetocin (42), isolated from the fermentation broth of Chaetomium minutum; [69] verticillins A (43), B, and C, obtained from Verticillium sp., exhibit antimicrobial activity against Gram-positive bacteria and potent antitumor activity in HeLa cell lines; [70][71][72] gliocladines A (44) and B (45); [24] 11,11'-dideoxyverticillin A and 11'-deoxyverticillin A; [24,73] melinacidins; [74][75][76] Sch52 900 and Sch52 901; [24] and some leptosins A (46), B (47), and C (48). [23] Leptosins C and F, isolated from the marine fungus Leptoshaeria sp., have inhibitory activity against topoisomerases I and II [77] (Scheme 2).…”
Section: Structure and Bioactivitymentioning
confidence: 99%
“…27 It has been suggested that autophagy relates to apotosis by acting as a partner, an antagonist or an enabler of apoptosis depending on cell type, stimulus and environment. 28,29 11'-deoxyverticillin A, a natural product isolated from the Cordyceps-colonizing fungus Gliocladium sp., 30 is a member of a class of fungal secondary metabolites known as epipolythiodioxopiperazines (ETPs). 31 The ETPs have been previously reported to have a broad range of biological activities including antimicrobial, antiparasitic, antiviral, immunosuppressive and/ or anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…De algunas cepas de G. roseum, se han aislado compuestos nematicidas [32] [33]. En el caso de G. butleri se conoce que produce una gran cantidad de quitosano, que se utiliza en agricultura como estimulante del crecimiento y la inmunidad, sin embargo las referencias a su capacidad nematicida son casi nulas [34].…”
Section: Megalosporum T Spirale Y T Asperellumunclassified